1992
DOI: 10.1002/jcb.240490206
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of histone H4 gene transcription during postnatal development in transgenic mice and at the onset of differentiation in transgenically derived calvarial osteoblast cultures

Abstract: In vivo regulation of cell cycle dependent human histone gene expression was examined in transgenic mice using a fusion construct containing 6.5 kB of a human H4 promoter linked to the chloramphenicol acetyltransferase (CAT) reporter gene. Transcriptional control of histone gene expression, as a function of proliferative activity, was determined. We established the relationship between DNA replication dependent H4 mRNA levels (Northern blot analysis) and H4 promoter activity (CAT assay) during postnatal develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
3
5
0
Order By: Relevance
“…Multiple histones (H2A, H2B, H4 and H1 histone-like protein) previously identified as downregulated during metacyclogenesis ( 65 , 66 ) were also identified as such in this analysis with H4 mRNA levels particularly depleted. The decrease in histone transcripts as the parasite enters the non-dividing stationary phase suggests a mode of regulation that is dependent on the cell cycle and is consistent with observations in higher eukaryotes that histone gene expression decreases in differentiated cells ( 67 , 68 ). Also consistent with previous findings, multiple β-tubulin family members were identified as downregulated ∼1.4-fold as the parasite becomes infective ( 69 ).…”
Section: Resultssupporting
confidence: 87%
“…Multiple histones (H2A, H2B, H4 and H1 histone-like protein) previously identified as downregulated during metacyclogenesis ( 65 , 66 ) were also identified as such in this analysis with H4 mRNA levels particularly depleted. The decrease in histone transcripts as the parasite enters the non-dividing stationary phase suggests a mode of regulation that is dependent on the cell cycle and is consistent with observations in higher eukaryotes that histone gene expression decreases in differentiated cells ( 67 , 68 ). Also consistent with previous findings, multiple β-tubulin family members were identified as downregulated ∼1.4-fold as the parasite becomes infective ( 69 ).…”
Section: Resultssupporting
confidence: 87%
“…The latter Hist1 cluster was later replicating in 8/8 committed cell types in mouse and 5/6 in human (not lymphoblasts), and includes several core histone genes that were downregulated up to 2.5-fold in NPCs. These results are intriguing in light of previous reports of histone downregulation during development [28], as well as a hyperdynamic chromatin phenotype in ESCs that involves higher exchange rates of histone H1 [29] and is required for efficient somatic cell nuclear reprogramming in Xenopus oocytes [30]. Importantly, all of the histone H1 genes are found in this cluster, suggesting that regulation of global H1 abundance may provide a mechanism for the overall chromatin compaction and consolidation of replication timing observed during neural differentiation [3][5].…”
Section: Resultssupporting
confidence: 62%
“…The LacZ expression pattern driven by the Hinfp promoter (Fig. 4) is comparable to results obtained with distinct transgenes under control of a representative human histone H4 promoter (Gerbaulet et al, 1992; van Wijnen et al, 1991). The latter studies revealed proliferation-related transgene expression reflecting histone H4 promoter activity in different mouse tissues and cell types, including cells from cranial tissues (e.g., calvaria, brain).…”
Section: Resultssupporting
confidence: 73%
“…This down regulation occurs presumably by destabilization of histone mRNA when DNA synthesis ceases upon completion of the first S phase (Osley, 1991; Stein et al, 1984). In vivo studies on histone H4 gene transcription have been limited to work with transgenic mice that focused on mid-gestation and later stages of fetal development in both osseous and non-osseous (e.g., liver, spleen) tissues (Gerbaulet et al, 1992; van Wijnen et al, 1991). In addition, a few studies have examined mouse histone H4 gene transcription in cultured cells (Seiler-Tuyns and Paterson, 1987; van der Meijden et al, 1998).…”
Section: Introductionmentioning
confidence: 99%